Impact of host factors and invasive meningococci on bacterial adhesion, proliferation, primary nasal epithelial barrier function, and immune response - Daan W. Arends; Debbie van Rooijen; Esther van Woudenbergh; Janine Wolf; Milou Ohm; Marien I. de Jonge; Gerco den Hartog (Microbiology Spectrum)
ABSTRACT Neisseria meningitidis colonizes the human upper airway mucosa, which can progress into invasive meningococcal disease (IMD) upon breaching the epithelial barrier. Some serogroups and lineages are associated with IMD, whereas others rarely infect patients. Although multiple virulence factors have been described, it is unclear what makes some lineages hyperinvasive. Here, we examined meningococcal infection of air-to-liquid interface (ALI)-differentiated primary epithelial cells to assess host- and strain-dependent differences in colonization that could explain hyperinvasiveness. Nasal epithelial cells from seven donors were infected with meningococcal reference strains and hyperinvasive clonal complex 11 (cc11) strains, including serogroup C, W, and an unencapsulated capsule null locus strain. We assessed transepithelial electrical resistance (TEER), bacterial binding and growth, and the epithelial cytokine response. Most donor-strain combinations induced a TEER drop, with higher bacterial loads generally associated with lower TEER, indicative of a more permeable epithelial barrier. Cc11 strains induced slightly lower TEER levels than other strains. Bacterial binding and growth were highly donor-strain dependent. The unencapsulated strain exhibited the highest binding, and MenW cc11 showed higher binding than the MenW reference strain, but the MenC strains showed no difference. Despite strain and donor variability, meningococcal infection universally induced cytokines CCL20, CXCL1, CXCL8, CXCL10, and IL-18, with significantly higher CCL20 levels 24 h post-MenW cc11 infection. Principal component analysis showed cytokine profiles were predominantly influenced by the epithelial cell donor rather than the meningococcal strain. In conclusion, our experimental model shows that the outcome of meningococcal infection of the epithelium is highly dependent on specific donor-strain interactions.IMPORTANCEInvasive meningococcal disease (IMD) outbreaks remain a significant disease burden, often caused by Neisseria meningitidis strains belonging to “hyperinvasive” lineages, such as clonal complex (cc) 11. To determine what factors contribute to the invasiveness of a meningococcal strain, we examined the initial stage of becoming invasive, the interaction between upper airway epithelium and the bacteria. To assess both the role of the infecting meningococcal strain and host epithelium composition, we used multiple meningococcal strains and nasal primary epithelial cells from several healthy individuals. Our observation of specific infection dynamics for each cell donor and meningococcal strain combination highlights the importance of both host and bacterial factors—and especially their interaction—in the determination of the outcome of meningococcal infection. Understanding these host-strain-specific effects could help to identify individuals at risk of IMD and meningococcal strains with future outbreak potential.